A failed coup d’état and the pending constitutional problems - Palomino Manchego, José F.; Paiva Goyburu, Dante (REVISTA ELECTRONICA IBEROAMERICANA, 2024)
This article analyzes the failed coup d’état carried out by President Pedro Castillo, which determined that Congress removed him from office and immediately became a criminal trial facing various complaints. The legacy of his brief period and the consequences of the change in management, assumed by his vice president, Dina Boluarte, have made it possible to notice latent deficiencies in the Peruvian political system, which despite having a Constitution that is 30 years old, has a limited political class and without a properly defined country project.In this sense, it is considered that some of these problems of the Peruvian political regime represent an opportunity for the academy to contribute with solutions and measures that favor the Constitutional State, which is threatened by the vagaries of the main authorities, who seem to act on the margins of serious national problems where insecurity and recession are the epicenter of unfavorable turbulence for the country.
Keywords: Coup d’état; Democracy; Governance; Constitutional Law; Constitution Politics